The impact of COVID-19 pandemic on influenza surveillance: A systematic review and meta-analysis - Sasidharanpillai Sabeena; Nagaraja Ravishankar; Sudandiradas Robin (Wolters Kluwer Medknow Publications, 2022)
Background: Influenza activity was reported to be below the seasonal levels during the Coronavirus disease-2019 (COVID-19) pandemic globally. However, during the severe acute respiratory syndrome corona virus-2 outbreak, the routine real-time surveillance of influenza-like illness and acute respiratory infection was adversely affected due to the changes in priorities, economic constraints, repurposing of hospitals for COVID care, and closure of outpatient services. Methods: A systematic review and meta-analysis were carried out to assess the pooled proportion of symptomatic cases tested for influenza virus before the current pandemic in 2019 and during the pandemic in 2020/21. An electronic search of PubMed/MEDLINE, Scopus, and Google Scholar was carried out for the articles reporting the impact of the COVID-19 pandemic on influenza surveillance among humans using search terms. The study was designed based on Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines and the meta-analysis was performed to synthesize the pooled proportion of patients sampled for influenza with 95% confidence interval (CI). Results: The nine qualified studies from the WHO European region, Canada, Japan, Germany, Italy, Spain, South Africa, and the United States were pooled by random-effects meta-analysis. The overall pooled proportion of symptomatic cases sampled for influenza surveillance before and during the pandemic was 2.38% (95% CI 2.08%-2.67%) and 4.18% (95% CI 3.8%-4.52%), respectively. However, the pooled proportion of samples tested for influenza before the pandemic was 0.69% (95% CI 0.45%-0.92%) and during the pandemic was 0.48% (95% CI 0.28%-0.68%) when studies from Canada were excluded. Conclusion: The meta-analysis concludes that globally there was a decline in influenza surveillance during the COVID-19 pandemic except in Canada.